Strategi Manajemen Krisis Mustika Ratu melalui Media Sosial Instagram : Studi Kasus pada Giveaway Paket Umroh - Marshanda Amelia Putri; Nabila Rahmawati; Nurfitriah Nurfitriah; Rizkiyah Rizkiyah; Tutik Ayu Fitriyaningsih; Nadya Poernamasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes Mustika Ratu’s crisis management strategy through Instagram social media, focusing on a case study of the umrah package giveaway. Using a qualitative approach with a case study, this study aims to deeply understand the process, challenges, and effectiveness of crisis management communication. Through content analysis of interaction observations on Instagram, the findings show that Mustika Ratu has successfully utilized the platform as the main means to respond to issues, build public trust, and maintain the company’s reputation when potential crises arise during the giveaway program. By using crisis management theory, the results of the study will discuss the pre-crisis, crisis and post-crisis processes. The results of the content analysis on the Mustika Ratu umrah package giveaway on Instagram show the implementation of a proactive crisis management strategy. How Mustika Ratu communicates to prevent or resolve potential problems (crises) that could arise from programs involving large prizes and sensitive spiritual values. Mustika Ratu shows efforts to prevent crises early on, before problems arise. Although this study did not find any major crises occurring, the analysis shows Mustika Ratu’s readiness to respond to potential complaints. After the crisis in this phase is also to maintain reputation and trust after the problem has been resolved.